Pricing Strategy of Supply Chains with Uncertain Remanufacturing Rate and WTP Discrepancy - Shu, Tong; Liu, Qi; Chen, Shou; Wang, Shouyang; Lai, Kin Keung (International Journal of Management and Sustainability, 2019)
A well-known conclusion in extant literature on remanufacturing is that the overall supply chain profits tend to be higher when the used products are recycled by the retailer. This article builds a model of a closed-loop supply chain consisting of a single retailer and a single manufacturer and analyzes the impact of recovery rate and remanufacturing rate on pricing strategy of closed-loop supply chains when consumer willingness to pay for new and remanufactured products differs. In the model, the retailer recycles all used products and the manufacturer exploits the used products recycled by the retailer to make remanufactured products. This article investigates the performance of supply chains with centralized and decentralized decisions, and the Stackelberg’s game model is deployed to find whether recovery rate and remanufacturing rate can significantly affect the product prices and output of supply chains when the consumer willingness to pay varies. Meanwhile, the rise in recovery rate and remanufacturing rate leads to increased overall profits in closed-loop supply chains. This further indicates that the optimal profits of closed-loop supply chains in centralized decisions are higher than those in decentralized decisions.